Variation in Seagrass Carbon Stocks Between Tropical Estuarine and Marine Mangrove-Fringed Creeks - Juma, Gabriel A.; Magana, Adiel M.; Michael, Githaiga N.; Kairo, James G. (Frontiers in Marine Science, 2020)
Seagrass and associated blue carbon ecosystems are important carbon sinks and hence understanding their spatial and temporal variability is vital in appreciating their potential roles in climate change mitigation and adaptation. Indo-Pacific region has the highest seagrass biodiversity yet little focus has been made to compare seagrass habitat extent and carbon dynamics with their temperate counterparts. The present study assessed habitat characteristics and seagrass species distribution, diversity and carbon storage in Eastern (marine) and Western (estuarine), mangrove fringed creeks of Gazi Bay, Kenya. Data on species composition, canopy cover, biomass and sediment organic carbon were collected in 80 plots of 0.25m by 0.25m laid along transects established perpendicular to the waterline. Five species formation viz; Thalassia hemprichii, Cymodocea rotundata, Cymodocea serrulata, Enhalus acoroides, and Thalassidendron ciliatum were encountered as either single or mixed stands. There was a significant difference in total seagrass biomass between creeks (p < 0.01) with Eastern creek recording a mean of 10.2 ± 0.6 Mg C ha-1 while Western creek recorded 4.3 ± 0.3 Mg C ha-1. In addition, sediment carbon to 1 m depth varied significantly (p < 0.01) between species in the two creeks and ranged from 98 – 302 Mg C ha-1, with the Eastern and Western creeks recording means of 258 ± 90 and 107 ± 21 Mg C ha-1 respectively. The total carbon stocks from 50 ha of seagrasses in Eastern creek was 13,420 Mg C; whereas in the 70 ha of Western creek, it was 7,769 Mg C. The study shows that seagrass community attributes such as species composition and productivity can vary dramatically over small spatial extent due to differences in biophysical conditions and cautions estimation of site-specific carbon stocks using generalized global values.